Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I know that $$ \int_{0}^{+ \infty} e^{- x^{2}} dx = \frac{\sqrt{\pi}}{2}. $$

My question is: $$ \int_{0}^{1} e^{- x^{2}} dx = ~? $$

share|cite|improve this question
I think one can only do it numerically. – Jack Sep 19 '11 at 3:36
Well, there are ways to numerically compute the error function, much as you'll need a numerical method to compute $\sin\,1$... – J. M. Sep 19 '11 at 3:40
See here: for more information. – Adam Saltz Sep 19 '11 at 3:52
up vote 3 down vote accepted

$\mathrm{erf}(z)$ is the "error function" encountered in integrating the normal distribution (which is a normalized form of the Gaussian function). It is an entire function defined by $$\mathrm{erf}(z)=\frac{2}{\sqrt{\pi}}\int_{0}^{z}e^{-t^2}\mathrm{dt}$$ Note that some authors (e.g., Whittaker and Watson 1990, p. 341) define $\mathrm{erf}(z)$ without the leading factor of $2/\sqrt{\pi}$.

Your question's solution is $$\int_{0}^{1}e^{-r^2}\mathrm{dr}=\frac{\sqrt{\pi}}{2}\mathrm{erf}(1)$$

You can get approximate value by using series $$\mathrm{erf}(x)=\frac{e^{-x^2}}{\sqrt{\pi}}\sum^{\infty}_{n=0}\frac{(2x)^{2n+1}}{(2n+1)!!}$$

Hope this helped.

Added. approximate value of $\mathrm{erf}(1)$ with 20 digits is


so the value is


share|cite|improve this answer
You could also use the series $$ \int_0^x e^{-r^2}\ dr = \sum_{k=0}^\infty \frac{(-1)^k x^{2k+1}}{k!(2k+1)}$$ – Robert Israel Sep 19 '11 at 4:35
I prefer the series ks0830 used to the usual Maclaurin series; it's less prone to subtractive cancellation. – J. M. Sep 19 '11 at 15:21
When I have to eveluate an alternating series like this, I either separately accumulate the positive and negative terms or see if, for large enough $n$, $a_{2n}-a_{2n+1}$ has constant sign. – marty cohen Dec 23 '12 at 22:13
@J.M.: I show these two methods and an asymptotic expansion here. – robjohn Dec 24 '12 at 9:57

Since $$ e^{-x^2}=\sum_{k=0}^\infty\frac{(-x^2)^k}{k!} $$ we get by integrating that $$ \int_0^te^{-x^2}\,\mathrm{d}x=\sum_{k=0}^\infty(-1)^k\frac{t^{2k+1}}{(2k+1)k!} $$ Therefore, $$ \int_0^1e^{-x^2}\,\mathrm{d}x=\sum_{k=0}^\infty\frac{(-1)^k}{(2k+1)k!} $$ which converges pretty quickly.

Unilateral Power Series

A bit more complicated, yet yielding a non-alternating series, is to note that if we define $$ f(x)=e^{x^2}\int_0^xe^{-t^2}\,\mathrm{d}t $$ Then $f'(x)=1+2xf(x)$ and $$ f(x)=\sum_{k=0}^\infty a_kx^k $$ yields $2a_{k-1}=(k+1)a_{k+1}$. Using $f(0)=0$ and $f'(0)=1$ gives $a_{2k+1}=\dfrac{2^k}{(2k+1)!!}$. Thus, $$ \int_0^xe^{-t^2}\,\mathrm{d}t=e^{-x^2}\sum_{k=0}^\infty\frac{2^kx^{2k+1}}{(2k+1)!!} $$ Therefore, $$ \int_0^1e^{-t^2}\,\mathrm{d}t=e^{-1}\sum_{k=0}^\infty\frac{2^k}{(2k+1)!!} $$

share|cite|improve this answer
Nice to see the double factorial popping up every so often... :) – J. M. Jan 16 '13 at 17:19

According to Laplace, Legendre and the two masters of continued fractions, Jacobi and Ramanujan, $$ \int_{0}^{1} e^{- x^{2}} \,d{x} = \frac{\sqrt{\pi}}{2} - \cfrac{\frac{1}{2} e^{-1}}{1 + \cfrac{1}{2 + \cfrac{2}{1 + \cfrac{3}{2 + \cfrac{4}{1 + \cfrac{5}{2 + \cdots}}}}}}. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.